Readiness of Information Security Management Systems (ISMS) policy on hospital staff using e-patuh system - Waidah Ismail; Alwi N.H.M.; Ismail R.; Bahari M.; Zakaria O. (Universiti Teknikal Malaysia Melaka, 2024)
Indexed by Scopus